MANAJEMEN PEMBIAYAAN DALAM PENINGKATAN MUTU PENDIDIKAN - Djuwairiyah; Abd. Muqit; Heni Listiana (Journal Multicultural of Islamic Education, 2021)
Educational institutions are institutions that allow to organize a structured and traditional learning process. In order to improve the quality of education, educational institutions must not only meet the standard criteria for providing education, but also must be supported by adequate administration costs. The management of this education fund must be based on the principles of fairness, efficiency, transparency, and accountability. Regarding the implementation of responsible and professional duties, Allah swt. Affirmed: verily Allah has commanded all of you to give a mandate to his members.